PROTECTION OF TRADE SECRETS IN UZBEKISTAN: ANALYSIS OF THE METAL-TECH LTD. v. REPUBLIC OF UZBEKISTAN CASE - Abdullaev , Oybek (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This thesis is devoted to the analysis of the Metal-Tech Ltd. v. Republic of Uzbekistan case (ICSID Case No. ARB/10/3, 2013) as a precedent in the field of international investment protection of trade secrets and know-how. The work consistently examines the factual circumstances of the dispute related to the creation of a joint venture for molybdenum processing in Uzbekistan, the legal regime of investments under the Israel–Uzbekistan bilateral investment treaty, and the mechanism for applying the requirement for the legality of investments in the context of the corruption component of the case. Special attention is paid to how the corruption payments identified by the arbitral tribunal deprived the investor of jurisdictional protection of technological assets, despite the formal inclusion of know-how in the concept of "investment" under the treaty. Based on the analysis of the decision, conclusions are formulated about systemic problems of trade secret protection in Uzbekistan and practical measures necessary for both foreign investors and the legislator.